Pengaruh promosi staycation terhadap keputusan tamu menginap di alila hotel seminyak saat pandemi covid-19 - Juniarta, Pande Putu (Jurnal Kepariwisataan dan Hospitalitas, 2021)
The development of tourism n ndonesia during the COVID-19 pandemic has experienced a very significant decline. Bali as a major tourist destination n ndonesia also experienced the same thing. This has a direct mpact on various sectors, especially the hotel accommodation sector. Many hotels are doing various ways in order to survive in this pandemic era by carrying out promotional strategies. One of the promotional strategies that s carried out is a staycation. Alila Hotel Seminyak is one of the hotels affected by the COVID-19 pandemic which is conducting a staycation promotion to attract tourists to stay at the hotel. This study aims to determine the effect of staycation promotions on guest decisions to stay at Alila Hotel Seminyak during the covid-19 pandemic era. The research method used n this research s descriptive quantitative with simple linear regression data analysis. The results of the research show that there is a significant nfluence between staycation promotions on guest decisions to stay at Alila Hotel Seminyak.